Islamic Educational Philosophy's View of Humans - Cindy Alya; Anisah Triyuliasari (Tahta Media Group, 2024)
This research aims to analyse the nature of man, the purpose of life, and the role of man in learning based on Islamic philosophical perspectives. The research explores how these concepts shape an Islamic educational approach that emphasises the development of the individual as a whole, empowerment, and fulfilment of human potential to create a moral and ethical human being who can combine knowledge with noble behaviour. The research method uses a qualitative approach with library research. Data collection techniques involved in-depth analyses of relevant literature, including academic journals, philosophy books, and scholarly writings on Islamic education and the concept of man. The data were analysed descriptively to understand and interpret the philosophical concept in the context of Islamic education. In the Islamic view, the results showed that humans are noble creatures before Allah SWT, with perfect physiques and extraordinary potential compared to other creatures. Humans consist of both body and mind, making them unique and cannot be treated like fully controlled robots. This research asserts that human development in Islamic education should include both physical and spiritual aspects balanced, including morals, ethics, spirituality and science. With their potential, human beings should be directed to achieve perfection as obedient servants of Allah and become individuals who benefit society and the environment. Understanding human nature from an Islamic perspective is an important basis for designing an effective and holistic Islamic education curriculum and approach.